2021
DOI: 10.1094/pdis-05-20-1054-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report on the Occurrence of an Aggressive Pathotype, 734, of Plasmopara halstedii Causing Sunflower Downy Mildew in Hungary

Abstract: Downy mildew of sunflower (Helianthus annuus L.) is caused by Plasmopara halstedii (Farl.) Berl. et de Toni, leading to significant losses in crop production worldwide. The number of new and more aggressive pathotypes has increased rapidly over the last 10 years in Europe (Virányi et al. 2015, Bán et al. 2018), therefore, constantly monitoring the distribution of races is an important task. As part of regular surveys in June 2019, severe downy mildew was identified in some regions, appearing as chlorotic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…This shows that isolates having the same code (i.e., 715) can lead to different reactions in some genotypes that are widely used in sunflower breeding for resistance to downy mildew (i.e., RHA-340) and suggests the need of updating the nine differentials that were internationally agreed upon more than 20 years ago to be utilized for race identification of P. halstedii. In any case, our results agree with those of other authors from the Czech Republic and Hungary [32,35,36] and confirm that the previously suggested widening of distribution of highly virulent P. halstedii races [2] is a reality in Europe.…”
Section: Discussionsupporting
confidence: 93%
“…This shows that isolates having the same code (i.e., 715) can lead to different reactions in some genotypes that are widely used in sunflower breeding for resistance to downy mildew (i.e., RHA-340) and suggests the need of updating the nine differentials that were internationally agreed upon more than 20 years ago to be utilized for race identification of P. halstedii. In any case, our results agree with those of other authors from the Czech Republic and Hungary [32,35,36] and confirm that the previously suggested widening of distribution of highly virulent P. halstedii races [2] is a reality in Europe.…”
Section: Discussionsupporting
confidence: 93%
“…The first high virulent pathotype (704) was isolated in 2010 by Rudolf et al [ 22 ] from two sunflower fields in Hungary. In the following years, our research team confirmed the increased distribution of pathotype 704 in the country [ 27 ] and the emergence of three new P. halstedii pathotypes, 714, 724, and 734 [ 13 , 14 , 28 ] (New records are separated from previously published records by bold isolate numbers in Table 3 .). Previously, pathotype 724 was only identified from Hungary, but according to our present results, it was also detected in Romanian samples in 2019.…”
Section: Discussionmentioning
confidence: 56%
“…Gulya [ 11 ] has previously reported on 35 pathotypes. More recently, new global and highly aggressive pathotypes of P. halstedii have been identified in some areas of Europe, such as pathotype 354 in Germany [ 12 ], 724 and 734 in Hungary [ 13 , 14 ], 705 in Spain [ 15 ], and 705 and 715 in the Czech Republic [ 16 ]. Altogether, there are as many as 50 pathotypes worldwide [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only one race, 100, was present, and was widely distributed across France. In recent years, downy mildew has become a serious problem for the sunflower crop in France; until 2008, only 16 out of 50 worldwide races had been detected in various regions, suggesting that the pathogen population has evolved rapidly, resulting in a high diversity in virulence [ 13 , 14 , 20 , 21 , 22 , 23 ]. Furthermore, the wide use of fungicide to control this plant pathogen has led to the development of resistant strains that have decreased the fungicide’s efficacy.…”
Section: Introductionmentioning
confidence: 99%